2016
DOI: 10.7172/2449-6634.jmcbem.2016.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Media Credibility Perception Among Millennials in Slovakia

Abstract: Communication professionals have been facing various challenges and one of them is how to win the audience. Past studies suggest that credibility could be the key. Therefore, credibility can be suggested as one of the key factors driving the traffi c of individuals to certain media. By gaining a better understanding of how Millennials perceive credibility, companies can more appropriately plan and execute successful media campaigns directed to this very important public. A survey with 190 respondents -Millenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…There seems to be a consensus that men tend to find media less credible than women (see, Choi et al, 2006; Eveland Jr & Shah, 2003; Johnson & Kay, 2002). Similar results were found in Slovakia, where a media credibility study found that ‘women are more likely to trust Slovak media than men’ (Vilčeková, 2015, p. 623). However, Shim et al (2015) found that women negatively associated media credibility with domestic television, international television, and the Internet.…”
Section: Gendersupporting
confidence: 74%
See 3 more Smart Citations
“…There seems to be a consensus that men tend to find media less credible than women (see, Choi et al, 2006; Eveland Jr & Shah, 2003; Johnson & Kay, 2002). Similar results were found in Slovakia, where a media credibility study found that ‘women are more likely to trust Slovak media than men’ (Vilčeková, 2015, p. 623). However, Shim et al (2015) found that women negatively associated media credibility with domestic television, international television, and the Internet.…”
Section: Gendersupporting
confidence: 74%
“…Credibility as a concept can be traced back to ancient Greece, where it was used to study persuasion techniques. Over time the introduction of radio, television, and the Internet has guided the evolution of credibility studies in modern times (Vilčeková, 2015). Modern-day credibility research dates back to the early 1950s with the seminal work of Hovland and Weiss (1951).…”
Section: The Concept Of Credibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Because they are online (almost) all the time (Stefko et al, 2019), it's natural for them to multitask and while watching TV, be involved in other digital activities simultaneously. Understanding how millennials perceive media credibility can support the planning and execution of successful media campaigns directed at this vital consumer group (Vilcekova, 2016). This phenomenon is referred to as multi-screening and has been explained by an earlier Google study (Google, 2012).…”
mentioning
confidence: 99%